PENGARUH LITERASI AGAMA ISLAM TERHADAP PRESTASI BELAJAR PAI DI SMK INSAN TEKNOKRAT BEKASI (Jaya Cimuning) - Jamiatul Maghfiroh; Acep Mulyadi; Rabiyannur Lubis (Turats, 2023)
This study aims to determine the effect of Islamic religious literacy on learning achievement in Islamic religious education at SMK Insan Technocrat Bekasi (Jaya Cimuning). This research is motivated by low Islamic religious literacy in students, due to the world of technology which is developing very rapidly, one of which is the lack of teacher strategies in applying Islamic religious literacy methods and in the field of entertainment, the rise of students today prefers to play online games and watch entertainment on television. Or smartphones that they have so that students' interest in reading and studying religion more deeply is reduced. Reading is a window to the world, by getting used to reading students will gain knowledge and insight or students' mindsets will become critical, and deepen the Islamic religion among teenagers or students at this time it is very necessary to become a guideline for akhlakul karimah according to the teachings of Islam applied in everyday life. This study uses quantitative research methods, and uses a survey research design with a correlational approach. The survey method is used to obtain data from certain natural places (not actions). Sampling in this study using simple random sampling technique. The research subjects were students of class X, while the object of this research was the Islamic religious literacy method. The population in this study were 14 students of class X at SMK Insan Teknokrat Bekasi (Jaya Cimuning) both male and female. The data collection technique used is a questionnaire or questionnaire with a rating scale of 1-5. The results of the study revealed that there was a significant correlation between the influence of Islamic religious literacy and student achievement in PAI at SMK Teknokrat Bekasi. This is shown by the coefficient (R) of 0.725 and the R Square value (coefficient of determination) of 0.526 which indicates that Islamic education learning achievement (Y) is influenced by Islamic religious literacy (X) of 52.6%, the remaining factors another 47.4% which gave "the influence of Islamic Education Learning Achievement of students at SMK Insan Teknorat Bekasi (Jaya Cimuning).